Major phenolic compounds, antioxidant, antimicrobial, and cytotoxic activities of Selinum carvifolia (L.) collected from different altitudes in India - Srivastava, Ravi Prakash; Kumar, Sachin; Singh, Lav; Madhukar, Mayank; Singh, Nitesh; Saxena, Gauri; Pandey, Shivaraman; Singh, Arpit; Devkota, Hari Prasad; Verma, Praveen C.; Shiva, Shatrughan; Malik, Sumira; et al. (Frontiers in Nutrition, 2023)
Antibiotic resistance poses a serious threat to public health, raising the number of diseases in the community. Recent research has shown that plant-derived phenolic compounds have strong antimicrobial, antifungal, and cytotoxic properties against a variety of microorganisms and work as great antioxidants in such treatments. The goal of the current work is to evaluate the anticancerous, antibacterial, antifungal, antioxidant, and cytotoxicity activities in the extracts of the different plant parts (leaves, stems, and roots) of S. carvifolia (L.) L. This is a medicinally important plant and has been used for different kinds of diseases and ailments such as hysteria and seizures. The phenolic compounds from the different plant parts were analyzed using HPLC and the following were found to be present: chlorogenic acid, gallic acid, rutin, syringic acid, vanillic acid, cinnamic acid, caffeic acid, and protocatechuic acid. Gallic acid was found to have the highest concentration (13.93 mg/g), while chlorogenic acid (0.25 mg/g) had the lowest. The maximum TPC value, which ranged from 33.79 to 57.95 mg GAE/g dry extract weight, was found in the stem. Root extract with 9.4 mg RE/g had the greatest TFC level. In the leaf and stem extracts, the RSC ranged from 0.747 mg/mL to 0.734 mg/1 mL GE/g dry extract weight, respectively. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was used to measure in vitro antioxidant activity. In a concentration-dependent way, promising antioxidant activity was reported. Moreover, 3,5-dinitrosalicylic acid (DNSA) and the Folin–Ciocalteu phenol reagent technique were used to determine reducing sugar content and total phenolic content, respectively. Antibacterial activity against eight strains (MIC: 250–1,000 μg/mL) was analyzed, and the stem extract exhibited maximum activity. Antifungal activity was also assessed, and potent activity was reported especially in the extract obtained from the stem. Cytotoxicity was evaluated using an MTT assay in the A549 cell line, where different doses (0.0625, 0.125, 0.25, 0.5, and 1 mg/mL) of leaf, root, and stem extracts were used. Treatment with these extracts reduced the cell viability, indicating that S. carvifolia may possess anticancer potential, which can be of great therapeutic value.